Study of Sediment Deposit Characteristics based on Geotechnical Properties and Geographic Information System (GIS) Approaches - Arif, Maulana; Fitriana, Fifin; Altiarika, Eka (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
Several sedimentation processes occur in the downstream area between river mouths and the sea. One of the effects of this sedimentation process is the occurrence of siltation around the coast. Not infrequently, this disrupts sea passages when the ship is about to head to the pier or go to sea. Kuala Beach is one of the locations in Pangkalpinang where the sedimentation process continues to occur enough to disrupt the smooth flow of sea traffic. This study aims to provide an overview and analysis of results related to sediment characteristics, spatial analysis of deposits, and predictions of deposition rates around Kuala Beach, Pangkalpinang City. This research was conducted using the following methods: 1) Method of investigating sediment characteristics by collecting data through field testing in the form of hand drills and laboratory testing, 2) Spatial analysis method by mapping the area of sedimentation based on the results of sediment characteristic tests using Agisoft Metashape and QGIS. The results of this study note that sediment deposits are dominated by sediments with sandy grain characteristics (SP symbol based on the Unified Soil Classification System) and a fine grain content (passing sieve number 200) of around 1-3%. The pattern of distribution of sediment deposits is known to have relatively flat contours and relatively uniform characteristics down to a depth of 1.5 m. The coefficient of grain uniformity (Cu) is in the range of 2.43-8.2 with the tendency of uniformity level getting higher to the southeast. The coefficient of grain gradation (Cc) is in the range of 0.44-1.64 with the tendency of the gradation level getting better to the southeast.